Traditional versus Blogosphere Information Landscapes: The Case of Diabetes and HbA1c - Black, Fiona; Amos, Kathleen; Boyd, Michael; Nielson, Ron; Theoret, Claude (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper compares two information landscapes in relation to an important measurement – glycated hemoglobin (HbA1c) – in the management of diabetes. Quantitative and qualitative analyses, including visualizations with lexical maps, facilitate new understandings about peer-reviewed research and the blogosphere in the evolution of physician knowledge and public opinion. Cet article compare deux paysages de l'information en relation avec une mesure importante, l'hémoglobine glyquée (HbA1c), dans la gestion du diabète. Des analyses quantitatives et qualitatives, y compris la visualisation avec cartes lexicales, permettent une nouvelle compréhension de la recherche arbitrée et de la blogosphère dans l'optique de l'évolution des connaissances des médecins et de l'opinion du public.